Analysis results for the effectiveness of monetary policies with cointegration and causality analyses - Dinçer, Hasan; Yüksel, Serhat (IGI Global, 2022)
The aim of this chapter is to examine the effectiveness of the monetary policies in E7 economies. For this purpose, two different variables are selected, which are central bank interest rate and inflation rate. These variables are tested with the help of Kao panel cointegration analysis, Pedroni panel cointegration analysis, and Dumitrescu Hurlin panel causality analysis. Additionally, monthly data of these variables for the periods between 1996:01-2019:02 is used in the analysis process. The findings show that there is a long-term relationship between interest rate and inflation rate for E7 economies. This situation gives information that monetary policies are used effectively in these countries. On the other side, for all three different lags, it is concluded that interest is the main cause of the inflation rate. This situation gives information that interest rate decisions of the central banks in E7 economies are very successful to control the inflation rate.
Keywords: Causality Analyses; Monetary Policies; Analysis Results